Reproductive state controls transcription in the murine liver, with implications for breast cancer liver metastasis - Michelle K. Ozaki; Yi Zhang; Alexandra Q. Bartlett; Elise de Wilde; Xiangnan Guan; Alex Yang; Zheng Xia; Pepper Schedin (Proceedings of the National Academy of Sciences, 2025)
Liver biology is functionally linked to lactation, as liver size and metabolic output increase during lactation to support synthesis of breast milk. Upon weaning, the rodent liver returns to baseline homeostasis via hepatocyte cell death, in a process considered liver involution. To explore liver biology changes across a lactation-wean cycle, we employed transcriptomic profiling. We identified elevated hepatocyte proliferation and anabolic metabolism gene signatures during lactation, consistent with the liver being a major producer of substrates needed for milk production. Rapid loss of these capacities upon weaning correlated with catabolic metabolism, lysosomal-mediated cell death, and an enrichment of immune-suppressive cells. Furthermore, we identified that the transcriptional profiles associated with liver involution share similarities with the gene expression patterns of liver premetastatic niches. This work identifies features of reproductive control of liver biology that set a foundation for better understanding the potential role of the liver in maternal health.